Recovery-Oriented Mental Health Practice in a Community Care Unit: An Exploratory Study. Issue 4 (October 2016) - McKenna, Brian; Oakes, Jane; Fourniotis, Niki; Toomey, Nigel; Furness, Trentham
Abstract : ABSTRACT: A recovery-oriented model of care has become the major focus of mental health service delivery in the state of Victoria, Australia. However, there is a total absence of knowledge of recovery-oriented mental health practice in community care units (CCUs). Therefore, the aims of this exploratory study were to: (a) describe what aspects of the current model of care fit within the domains of recovery; and (b) describe the pragmatic processes that staff use to mold their care within the domains of recovery. Twenty-one key stakeholders provided informed voluntary consent to participate in one-to-one interviews. Six content domains evolved to include: (a) a common vision: "a continuous journey"; (b) promoting hope; (c) promoting autonomy and self-determination; (d) meaningful engagement; (e) holistic and personalized care; and (f) community participation and citizenship. The CCU appeared to be on a journey of transformation toward personal recovery. However, clinicians were grappling with an identified tension among personal recovery and clinical recovery. The tension among personal recovery and clinical recovery may be attributed to the psychosocial rehabilitation model of care, which was previously systemic in Victorian CCUs.